Web-based mind learning system using mind mapping and mind scheduling. (28th July 2005) - Kwan, Irene; Fong, Joseph; Chan, Fion; Ngan, Jim
Distance learning and life-long studying have become popular in Hong Kong. To better balance the time allocation between job and study, students have to plan their study carefully. They need a full picture of the course material, the course schedule, course interactions and guidelines for such planning. We adopt practical advice, methodologies and techniques to develop a web-based mind learning system with mind scheduling and mind mapping. Mind scheduling provides the administrator, instructor and student with the scheduling methods underlying the principles of the mind and schedule paradigms, which offers a good way of time management in a semester. Mind mapping consists of a map tile, which holds the subject the map by filling in the thoughts the user may have about the subject, describing that thought in more detail. Thus, course leaders, lecturers, administrators and students can collaboratively use this system anytime and anywhere to supplement classroom learning for better coherence between students and lecturers.